Ensibuuko uses digitalisation to support rural savings and loans cooperatives in Uganda - Otim, Gerald (Technical Centre for Agricultural and Rural Cooperation, 2018)
Gerald Otim, Founder and CEO of Ensibuuko (Uganda), takes us through the evolution of the company since their participation in CTA s AgriHack Championship in 2013.